A comparative study on effect of aromatic polyimide chain conformation on reinforcement of carbon nanotube/polyimide nanocomposites. Issue 13 (1st February 2014) - Zhang, Baode; Chakoli, Ali Nabipour; Zang, Wanchen; Tian, Yanqing; Zhang, Ke; Chen, Chunhai; Li, Yao
ABSTRACT Two kinds of polyimides (PIs) were selected as matrices for multiwalled carbon nanotubes (CNTs)‐based nanocomposites. The two PIs were initially synthesized through reactions of a same benzoxazole‐containing diamine with two different dianhydrids. A linear PI was formed from the ether bond‐containing dianhydride, while a nonlinear PI was formed from the C(CF3)2− groups containing dianhydride. Optimized dispersion of nanotubes in both kinds of PIs was found to be at a concentration with 0.5 wt % COOH‐CNT, where great enhancement was achieved for both PIs. It was also found that introducing nanotubes into PI matrices aroused more significant increase of Young's modulus and break stress in linear PI than that in nonlinear PI. To determine the key parameters involved in design of PIs for maximum reinforcement efficiency using CNT as the nanofiller, the nanoscopic dispersion state of the nanotubes in diamine solution and their reaction were investigated via morphological and spectroscopic studies. The interfacial interactions between nanotubes and two PI chains were characterized by FT‐IR and Raman spectroscopy. The fracture surface characteristics of two series of CNT/PI nanocomposites were further investigated using SEM. Our findings show that the diamine plays a double role for the in‐situ polymerization, a dispersant to disentangle the CNT agglomerates and a monomer for PI synthesis with dianhydrides. It was also found that geometry and flexibility of PI chains are crucial to determine the interfacial interactions between nanotubes and PI chains. For elucidating the different interfacial characteristics of the two PIs on the surface of CNT, we proposed a model for preferred conformation adopted by a single PI chain on a single CNT. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40479.